MENINGKATKAN KETERAMPILAN MEMOTONG KUKU MELALUI METODE DEMONSTRASI BAGI ANAK TUNAGRAHITA RINGAN - Yusfidarwati - - (Universitas Negeri Padang, 2012)
This research aim to to increase cross cut skill of nail to child of Tunagrahita Light through method demonstrate in Study of Education Help Ownself ( PMDS), at class student of III SLB.C Town of Payakumbuh. This research in form of research of Action Class that goes to during two cycle. Each consist of cycle of I , five times meeting, cycle of II four times meeting. Result of research is the happening of cross cut improving of skill of child nail of Tunagrahita Light without in assisting others. Through demonstration method can improve skill to cut child nail of Tunagrahita Light.